M. Dufrenne on Aesthetic Object - Parulskienė, Vijolė (Problemos, 1983)
The concept of “aesthetic object” in the interpretation of art work existence is specified and its relation to other concepts essential for phenomenological explanation of aesthetic experience in the works by M. Dufrenne, a French scientist, is revealed. The aesthetic object as a perceived work of art is considered to be an intentional product of consciousness. Autonomy and self-sufficiency are the essential features of the aesthetic object.